HUBUNGAN INTERAKSI SOSIAL DENGAN HASIL BELAJAR GEOGRAFI SISWA DI SMA NEGERI 1 KOTO XI TARUSAN - dora ayusti; Khairani Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The purpose of this reseach is to find out and discuss about the relationship between social interaction with the geography learning outcomes of students at Koto XI Tarusan 1 High School. the type of this research is descriptive correlational research. The population and the sample from this research is going to the students grade X.iis, XI.iis and XII. ips at Koto XI Tarusan 1 Public High School, the population in this research is around 428 of students and the sample is around 81 students. The withdrawal technique sample commonly uses a Stratified Random Sampling. Performed with the Slovin approachment, students of grade X with 22 of students, grade XI with 29 of students ,and grade XII with 30 of students. The technique for the Data collection was donw through the observation, documentation and fill of several questionnaires that already provided previously. desriptive statistics is one way to analyisis of data wich was used for this research. by using corelation pattern of product moment. The results from this research showed that there was a strong relations among social interaction with the geography of students for learning outcomes at Koto XI Tarusan 1 High School.